Perbandingan Prediksi Jumlah Wisatawan Menggunakan Metode Weighted Moving Average dan Simple Moving Average - Ida Darwati (Evolusi : Jurnal Sains dan Manajemen, 2025)
lang Regency and there are many other tourist attractions in various regions in East Java. Visitors who come are not only local residents, but also from outside the Malang Regency area. Good and complete services and facilities are very important so that visitors have the desire to come back. This is related to the readiness of the relevant parties so it is important to know how many visitors will come. In this research, the author predicts the number of tourists in the next period using the Simple Moving Average and Weighted Moving Average methods to find the best method between the two methods. For data processing the author uses the Python programming language with Jupyter Notebook. In this research, the best method was found, namely the Weighted Moving Average method with a smaller RMSE than using the Simple Moving Average method, then the author created a program design using a streamlit framework with the Weighted Moving Average method to find out the prediction of the number of tourists in Malang Regency in the following period.